Efektivitas Bimbingan Kelompok Teknik Sinema Edukasi Untuk Meningkatkan Motivasi Melanjutkan Studi pada Siswa SMK - Farijah, Lili; Noviyanti, Ade Irma; Mawaddati, Ika Romika (INSIGHT: Jurnal Bimbingan Konseling, 2025)
Innovative solutions are needed to address the problem of low motivation to continue studying among vocational high school students. The main contributing factors are an unsupportive environment, a lack of inspirational figures, and insufficient information. This study aims to determine how effective educational films can be in motivating eleventh-grade students at SMK NU 1 Pesanggaran to continue their education. The methodology employed was a pre-experimental design with a single-group pretest-posttest design. Eight out of 27 eleventh-grade students were selected as the research sample through purposive sampling. Student motivation to continue their education was used as the instrument, measured before and after the educational film intervention. Based on the research findings, the majority of students' motivation levels increased after receiving the intervention. Educational films are a useful tool for inspiring students to pursue higher education.